Linking childhood emotional neglect to adolescents' parent-related loneliness: Self-other differentiation and emotional detachment from parents as mediators. (December 2021) - Musetti, Alessandro; Grazia, Valentina; Manari, Tommaso; Terrone, Grazia; Corsano, Paola
Abstract: Background: The detrimental role of childhood emotional neglect (CEN) on long-term affective and social development has received increasing attention in the literature. Individuals who were emotionally neglected during their childhood are more prone to feeling isolated and excluded by their parent during adolescence. However, little is known about the mediating processes underlying this association. Objective: This study investigated whether self–other differentiation (SOD) and emotional detachment from parents mediate the link between CEN and parent-related loneliness. Method and participants: A sample of 535 high school students aged 13–18 years (63.6% female; M age = 16.21; SD = 1.40) completed questionnaires regarding demographics, CEN, SOD, emotional detachment, and parent-related loneliness. Results: After controlling for demographic covariates, structural equation modeling (SEM) showed that (a) CEN was positively associated with parent-related loneliness (β = 0.64, p < .001), (b) SOD did not mediate the relationship between CEN and parent-related loneliness (β = −0.01, p = .142), (c) emotional detachment partially mediated the relationship between CEN and parent-related loneliness (β = 0.16, p < .001), and (d) SOD and emotional detachment partially and sequentially mediated the link between CEN and parent-related loneliness, albeit with a small effect size (β = 0.02, p = .027). Conclusions: The findings underscore the significance of the link between CEN and parent-related loneliness in adolescence. Moreover, our results suggest that some adolescents with a history of CEN have difficulties in establishing clear boundaries between "self" and "other" and tend to engage in emotionally detached relationships with their parents, which may lead them to feel more parent-related loneliness. Clinical implications and directions for future research are discussed.